Absurdity and Injustice in Human Life in Franz Kafka's The Trial Directorate of the Federal Ministry of Education in Erbil - Khalaf, Faysal Ali (International Journal of Psychosocial Rehabilitation, 2020)
This paper examines the absurdity of life and the impossibility of justice in Franz Kafka's The Trial (1924) which is a coherent philosophical novel, simulating the futility of human action in a futile world accusing the individual of sins, this individual has no choice in. The protagonist finds himself in a bitter struggle against very vague judicial procedures. This novel, seemingly absurd, has always continued to arouse very diverse interpretations. It could be a report of a bureaucratic inhumanity, a warning of totalitarianism, or a metaphorical expression of anti-Semitism. Between this and that, this novel is seen as a handle of the absurd and surreal mood.